Training and Education of Detectives: (Real) Need or Mere Formality - Siniša, Đukić; Gostimirović, Ladin (NBP. Nauka, bezbednosti, policija, 2024)
This paper examines the issue of training and education of detectives as one of the prerequisites for high-quality and efficient performance of detective work. It is considered that the training should be, to the greatest extent possible, adapted to specific jobs and areas of detective work. Also, training should be part of the overall process of integrating detectives into the security system, that is, the private security sector. The concepts of detective training differ from country to country in terms of the content and structure of the program, duration, organization of implementation or non-implementation, which all together makes it very difficult to compare the results. There is no absolute standardization in this area, as well as relevant research on this topic and related areas. In this regard, the authors emphasize that detective training is an insufficiently researched issue that should be given much more attention. For the purposes of this paper, a comparative legal analysis of the legal regulations and by-laws that treat the models of detective training in Bosnia and Herzegovina and the surrounding countries - the Republic of Serbia, Montenegro and the Republic of Croatia - was performed. Based on the analysis, it can be concluded that different systems of training and education of candidates are in force, from the classic model where the curriculum is implemented according to the subject-modular concept, to mentoring work and internship practice. The aim of this work is to encourage a more comprehensive study of the training and education of detectives and to propose more adequate models suitable for the current time and the detective field of work.
Keywords: Detective work; training; detectives; legislation